Representation of Feminism in Sipatmo Dance: A Roland Barthes Semiotic Analysis (Oratio Directa, 2021)
This study examines representations of feminism in Sipatmo dance through Roland Barthes' semiotics. Sipatmo is a Betawi dance shaped by Chinese cultural influence and historically performed in religious ceremonies before developing into a stage performance. The study uses a qualitative approach based on documentation, video observation, and literature review conducted from February to July 2019. Denotation, connotation, and myth are examined in three costume elements and seven movement signs. The findings identify the crown, earrings, scarf, soja, ngawen, tipis, japin, nindak siliwang, lenggang tumpang depan, and tapak dua as signs associated by the researchers with dignity, beauty, respect, self-presentation, speech, self-protection, and spirituality. These interpretations show how performance signs may communicate ideas about women's agency, while also remaining dependent on cultural convention and the researchers' reading of the dance.
Keywords: Feminist representation; Semiotics; Roland Barthes; Sipatmo dance; Betawi culture